URGENSITAS OMBUDSMAN DALAM PENGAWASAN PELAYANAN PUBLIK - Nurul Laili Fadhilah (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2015)
Abstract: competition some areas as improving the quality of services and satisfaction of the people became the target of the government’s success in serving the community. Ombudsman to monitor the implementation of public service held by the organizer of state and government at both central and local levels including those organized by the State Owned Enterprises, Regional-Owned Enter-prises and State Owned Legal Entity as well as private entities or individuals who were given the task of organizing certain public services , The establishment of Ombudsman background for the empow-erment of people concerned about state administration, the implementation of the idea of democ-racy, and as a protection of the rights of community members. The apparatus of government, includ-ing the judiciary in charge of creating justice and prosperity. The existence of supervisor institution for public services to the community can be a means of control of people or institutions to maintain the quality of government services.Keywords: decentralization, public services, obudsman